2015
DOI: 10.1136/jnnp-2015-312379.180
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility Weighted Imaging to Detect Nigral Iron Accumulation in Parkinson's Disease

Abstract: IntroductionDopaminergic neuron loss in substantia nigra (SN) in patients with PD is associated with deposits of iron. Susceptibility weighted imaging (SWI) is a high-resolution MR-based imaging technique for quantifying iron depositions in vivo. SWI may be a robust biomarker for clinical characterization of PD.MethodsForty-two patients with PD were studied with SWI imaging. Average phase shift (radians) and percentage iron deposition of the SN were analysed using SPIN software. SWI data were also compared bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It has been shown that abnormal metabolism of brain iron results in abnormal iron deposition in PD, which may contribute to the damage of dopaminergic neurons and the occurrence of typical clinicopathological lesions of PD. In addition, abnormal iron deposition can be detected using iron‐sensitive magnetic resonance imaging (MRI) . It is thought that, as the prodromal stage of α‐synucleinopathies, iRBD patients may also have increased iron deposition in the brain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that abnormal metabolism of brain iron results in abnormal iron deposition in PD, which may contribute to the damage of dopaminergic neurons and the occurrence of typical clinicopathological lesions of PD. In addition, abnormal iron deposition can be detected using iron‐sensitive magnetic resonance imaging (MRI) . It is thought that, as the prodromal stage of α‐synucleinopathies, iRBD patients may also have increased iron deposition in the brain.…”
mentioning
confidence: 99%
“…In addition, abnormal iron deposition can be detected using iron-sensitive magnetic resonance imaging (MRI). [7][8][9][10] It is thought that, as the prodromal stage of α-synucleinopathies, iRBD patients may also have increased iron deposition in the brain. A recent susceptibility weighted-imaging (SWI) study found loss of dorsolateral nigral hyperintensity in two-thirds of iRBD patients.…”
mentioning
confidence: 99%
“…Several histological and radiological studies have reported an increased iron concentration in the deep nuclei of patients with PD, especially the SN. [19][20][21] QSM allows for the quantification of tissue iron content and could be sensitive to microstructural abnormalities in neurodegenerative disease. 22 The STN is a key nucleus in the functional control of motor activity in the basal ganglia by receiving GABAergic inhibitory projections from the globus pallidus externa (GPe).…”
Section: Discussionmentioning
confidence: 99%